ANALISIS KELAYAKAN USAHA PELAYANAN JASA TRAKTOR TANGAN DI KECAMATAN WELERI KABUPATEN KENDAL - Candra Wijayanto; Lutfi Aris Sasongko; Eka Dewi Nurjayanti (Universitas Wahid Hasyim, 2017)
The study was conducted in the Weleri District which is one of the center of users hand tractors to cultivate rice field in Kendal Regency. This study aims to find out how much cost, revenue, and income, as well as the feasibility of Hand Tractor Business Services in Weleri District Kendal Regency. The basic method used is descriptive analysis, while the research areas is determined purposively. Respondent sampling is using census method earn in as much as 42 owners of hand tractor Business Services that located in the Weleri district. Data were collected through interviews, recording, observation and questionnaires. Total average cost Hand Tractor Business Services of Rp 3,545,347,10 within one period of cultivate land and the average amount of receipts of Rp 6.053.142,88. Average income of Hand Tractor Business Services is Rp 2.507.795,78 Hand Tractor Business Services in Weleri District Kendal Regency is feasible seen from BEP volume out put of 1,06 ha smaller than the average of land that cultivated by owners hand tractor is 8,56 and RC ratio> 1 is 1,71 so that the business is feasible to be done. Keywords: Cultivation Feasibility, Hand Tractor Business Service.